Ambulatory Hemodialysis-Technology Landscape and Potential for Patient-Centered Treatment - Hojs, Nina (Clin J Am Soc Nephrol, 2020)
CKD is a worldwide health problem and the number of patients requiring kidney replacement therapy is rising. In the United States, most patients with ESKD rely on in-center hemodialysis, which is burdensome and does not provide the same long-term benefits as kidney transplantation. Intensive hemodialysis treatments have demonstrated improved clinical outcomes, but its wider adoption is limited by equipment complexity and patient apprehension. Ambulatory devices for hemodialysis offer the potential for self-care treatment outside the clinical setting as well as frequent and prolonged sessions. This article explains the motivation for ambulatory hemodialysis and provides an overview of the necessary features of key technologies that will be the basis for new wearable and implantable devices. Early work by pioneers of hemodialysis is described followed by recent experience using a wearable unit on patients. Finally, ongoing efforts to develop an implantable device for kidney replacement and its potential for implantable hemodialysis are presented.